Industrialization performance and regional independence on economic growth in sidoarjo district - Muhammad Yasin; Kunto Inggit Gunawan (Jurnal Scientia, 2024)
Study This intended For deepen How industrialization Which become pusher economy something region Because every industrialization in area Sidoarjo become a driving force in other industrial sectors and independence performance becomes a benchmark finance in Sidoarjo Regency has become so with industrialization and independent performance for awaken Growth Economy . Done with channel 1) Research linkages Industrialization on economic growth in Sidoarjo Regency, 2) Examining the relationship Performance Independence to Growth Economy in Regency Sidoarjo. aims: 1. Analyze in a way descriptive Influence Performance Industrialization of Economic growth in Sidoarjo Regency. 2. Analyze descriptively The Influence of Independence Performance on Economic Growth in Sidoarjo Regency. Data analysis in this research used the PLS ( Partial Least Square ) program application version 3.0 M3 PLS ( Partial Least Square ) developed First time by wold as method general For estimate the path model that uses construct latent with mutype indicator. Results of Independence Performance on Economic Growth in Sodoarjo Regency is significant with t-statistics as big as 2,369 (>1.96) while Industrialization on Economic Growth in Sidoarjo Regency is No significant with a t-statistic of 0.062 (<1.96).